Stem‐Cell Therapy for Esophageal Anastomotic Leakage by Autografting Stromal Cells in Fibrin Scaffold. (27th February 2019) - Xue, Xiang; Yan, Yan; Ma, Ye; Yuan, Yang; Li, Chunguang; Lang, Xilong; Xu, Zhiyun; Chen, Hezhong; Zhang, Hao
Abstract: Esophageal anastomotic leakage (EAL) is a devastating complication for esophagectomy but the available therapies are unsatisfactory. Due to the healing effects of mesenchymal stromal cells (MSCs) and supporting capability of fibrin scaffold (FS), we evaluated the efficacy of a stem‐cell therapy for EAL by engrafting adult and autologous MSCs (AAMSCs) in FS and investigated the potential mechanism. Twenty‐one rabbits were assigned to AAMSC/FS group ( n = 12) and control group ( n = 9). After harvested, AAMSCs were identified and then labeled with lenti.GFP. To construct EAL model, a polyethylene tube was indwelled through the anastomosis for 1 week. A total of 2 × 106 AAMSCs in 0.2 ml FS were engrafted onto the EAL for the AAMSC/FS group, whereas FS was injected for control. Magnetic Resonance Imaging (MRI) examination was performed after 5 weeks. Esophageal tissues were harvested for macroscopic, histological analyses, Western blot, and immunohistochemistry at 8 weeks. The animal model of EAL was established successfully. MRI scanning revealed a decreased inflammation reaction in AAMSC/FS group. Accordingly, AAMSC/FS group presented a higher closure rate (83.3% vs. 11.1%, p = .02) and lower infection rate (33.3% vs. 88.9%, p = .02). Histological analyses showed the autografted MSCs resided in the injection site. Furthermore, milder inflammation responses and less collagen deposition were observed in AAMSC/FS group. Western blot and immunohistochemistry studies suggested that the therapeutic effect might be related to the secretions of IL‐10 and MMP‐9. Engrafting AAMSCs in FS could be a promising therapeutic strategy for the treatment of EAL by suppressing inflammation response and alleviating fibrosis progression.Stem Cells Translational Medicine 2019;8:548–556 Abstract : Schematic overview of actives of adult and autologous mesenchymal stromal cells in fibrin scaffold in the treatment of esophageal anastomotic leakage.